The impact of attentional, linguistic, and visual features during object naming - Clarke, Alasdair D.; Coco, Moreno I.; Keller, Frank (Frontiers in Psychology, 2013)
Object detection and identification are fundamental visual tasks and recent work suggests that it is primarily objects, rather than low-level salient regions, that attract our attention. This raises the question of which objects are important in the context of a visual scene. The current eye-tracking study investigates how different features (attentional, visual and linguistic) influence the likelihood that a given object in a scene will be named. We carried out an object naming task involving 24 participants and 100 photographic images covering a wide variety of scenes. Images were displayed for five seconds. Then the image was removed, and participants had to name objects that had been present in the scene. We find that the amount of visual attention directed towards an object, its position and saliency, along with linguistic factors such as word frequency, animacy, and semantic proximity, all significantly influence whether it will be selected for naming or not.